Efficient Bargaining in a Dynamic Macroeconomic Model - Oliver Claas; Volker Böhm (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper analyzes the implications of bilateral bargaining over wages and employment between a producer and a union representing a finite number of identical workers in a monetary macroeconomic model of the AS AD type with government activity. Wages and aggregate employment levels are set according to an efficient (Nash) bargaining agreement while the commodity market is cleared in a competitive way. It is shown that, for each level of union power, measured by the share it obtains of the total production surplus, efficient bargaining implies no efficiency loss in production. However, due to the price feedback from the commodity market and to income-induced demand effects, all temporary equilibria with a positive labor share are not Nash bargaining-efficient with respect to the set of feasible temporary equilibrium allocations. The dynamic evolution of money balances, prices, and wages is analyzed being driven primarily by government budget deficits and expectations by consumers. It is shown that for each fixed level of union power, the features of the dynamics under perfect foresight are structurally identical to those of the same economy under competitive wage and price setting, i.e. for small levels of government demand, there exist two balanced paths generically, one of which with high employment and production is always unstable while the other one may be stable or unstable.
Keywords: C78; E24; E31; 330